THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK SATISFACTION AND GENERATION Y CHARACTERISTICS OF EMPLOYEE PERFORMANCE (Case Study at DKI Jakarta Regional Office BPJS Employment) - Teguh Budi Santoso; Tjiptogoro Dinarjo Soehari (Dinasti International Journal of Education Management And Social Science, 2020)
Abstract, the current composition of employees in the workplace by generation is dominated by Generation Y or Millennial Generation, and will continue to grow and even generation Z will emerge as the next generation that will enter the working age. Companies are required to adapt to all matters relating to this generation to maintain continuity and to improve performance. This study aims to examine and analyze the influence of organizational culture, generation Y characteristics and job satisfaction as a mediator on the performance of Generation Y employees at the Jakarta Regional Office Employment BPJS. The focus of the study is generation Y which is the largest population of employees. This type of research is quantitative research with the sampling method used is simple random sampling. The population is all employees of Generation Y BPJS at the Regional Office of DKI Jakarta and by using the Slovin formula a sample of 237 people is obtained. The analytical method used in this study is Structural Equation Modeling (SEM). The conclusion of the study shows that the characteristics of generation Y, job satisfaction, and organizational culture and job satisfaction significantly influence employee performance. Partially Y generation characteristics and organizational culture influence employee performance by moderating job satisfaction variables. Based on the results of the study it is suggested that BPJS Manpower management pay attention to the Y behavior characteristics of the workplace so that they are comfortable and productive, maintain a work culture focused on results, eliminate communication boundaries between generations, increase innovation participation for employees. Of the four variables, the employee performance variable has the highest average value among other variables, while the strong performance indicators are service level agreement and accuracy. Keywords: Y generation characteristics, organizational culture, job satisfaction and employee performance